High-Survival Rate After Microinjection of Mouse Oocytes and Early Embryos With mRNA by Combining a Tip Pipette and Piezoelectric-Assisted Micromanipulator - Chen, Lei-Ning; Fan, Xiao-Yan; Liu, Yi-Tong; Chen, Shao-Qing; Xie, Feng-Yun; Zeng, Li; Wen, Juan; Li, Jin; Ma, Jun-Yu; Ou, Xiang-Hong; Luo, Shi-Ming; Guo, Lei (Frontiers in Cell and Developmental Biology, 2021)
Utilizing microinjection to introduce biological molecules such as DNA, mRNA, siRNA, and proteins into the cell is well established to study oocyte maturation and early embryo development in vitro. However, microinjection is an empirical technology. The cellular survival after microinjection is mainly dependent on the operator, and an experienced operator should be trained for a long time, from several months to years. Optimizing the microinjection to be highly efficient and quickly learned should be helpful for new operators and some newly established laboratories. Here, we combined the tip pipette and piezo-assisted micromanipulator to microinject the oocyte and early embryos at different stages of mouse. The results showed that the survival rate after microinjection was more than 85% for cumulus-oocyte complex, germinal vesicle oocyte, 2-cell, and 4-cell embryos, and close to 100% for MII oocyte and zygotes. The high-rate survival of microinjection can save many experimental samples. Thus, it should be helpful for studying some rare animal models such as aging and conditional gene knockout mice. Furthermore, our protocol is much easier to learn for new operators, who can usually master the method proficiently after several training times. Therefore, we would like to publicly share this experience, which will help some novices master microinjection skillfully and save many laboratory animals.